INVESTIGATIONS ON THE EURO AREA PUBLIC DEBT CRISIS: THE CASE OF PIIGS - Cukurcayir, Sinan; Tezcan, Keramettin (European Scientific Journal, ESJ, 2013)
The crisis that emerged following the bankruptcy of Lehman Brothers which is the fourth largest investment bank in the United States quickly spread to the entire world and has globally become a financial and real sector crisis. Today, the global financial crisis has influenced many countries in the world, and caused various economic, political and social problems in the European Union countries especially in Greece, Italy, Ireland, Portugal and Spain (PIIGS). The global financial crisis became the European Union’s economic crisis at first, and later turned into to be the debt crisis of the Euro area. The decline observed in recent years in the economic performance of the countries of the Euro Area has become more apparent along with the economic crisis, and this situation increased the concern about the future of the Economic and Monetary Union. In this context, in this study within the framework of global capitalism, the economic, social and political problems that the global financial crisis caused in many countries are examined, observations were made on the Euro area public debt crisis and analyses were carried out on the PIIGS economies.